The Positive Externalities of Social Capital: Benefiting from Senior Brokers - Galunic, Charles; Ertug, Gokhan; Gargiulo, Martin (Academy of Management Journal, 2012)
The importance of an actor's network to his/her private benefits is well explored. Less well understood are the positive externalities of an actor's social capital—that is, whether it spills over and improves the outcomes of those to whom he or she is connected, creating broader, not just private, benefits. This study examines how investment bankers add value to one another in the course of everyday work. Our concern is with a banker's second-order social capital. The main question is whether being connected to a broker matters to the ability of a focal actor to add value to those around him/her. We argue and find that the importance of connecting to a broker is contingent on the broker's seniority relative to the focal actor. Networks of contacts who are of higher rank and/or the focal actor's leader positively contribute to the ability of the focal actor to add value. Second-order social capital does matter, when contacts are senior brokers.